2017
DOI: 10.1115/1.4035994
|View full text |Cite
|
Sign up to set email alerts
|

Improving Prediction of Flapping-Wing Motion By Incorporating Actuator Constraints With Models of Aerodynamic Loads Using In-Flight Data

Abstract: Flapping-wing flight is a challenging system integration problem for designers due to tight coupling between propulsion and flexible wing subsystems with variable kinematics. High fidelity models that capture all the subsystem interactions are computationally expensive and too complex for design space exploration and optimization studies. A combination of simplified modeling and validation with experimental data offers a more tractable approach to system design and integration, which maintains acceptable accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…It was determined that the wings move out of phase with the leading edge of the wing as the wing surface experiences torsion, which was consistent with other findings. 69,70 Additionally, both mechanical and electrical testing were performed. It was previously found that the bi-axial strain in the wing as well as the instantaneous thrust profile can be correlated with the percent change in power generated by wing-integrated solar cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined that the wings move out of phase with the leading edge of the wing as the wing surface experiences torsion, which was consistent with other findings. 69,70 Additionally, both mechanical and electrical testing were performed. It was previously found that the bi-axial strain in the wing as well as the instantaneous thrust profile can be correlated with the percent change in power generated by wing-integrated solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…We previously measured and modeled a significant reduction in flapping amplitude with flapping frequency due to torque limitations of the servo motor. 70 The heavier and stiffer wings and greater forces generated by the wings also end up in a higher reduction in flapping amplitude. This can also be seen in the comparison of the thrust model in equations (24) and (25) with the test stand measurements, seen in Figure 10.…”
Section: Configuration Of Solar Cells In Wings and Wind Tunnel Measurmentioning
confidence: 99%
“…Details regarding system design issues, such as the actuator and wing coupling, have been investigated in other work. 53 Therefore, new approaches are needed to augment thrust production in FWAVs.…”
Section: Flapping Frequency Dependence On Actuator Performancementioning
confidence: 99%
“…29 Following the collection of experimental data of flying vehicles, a new formulation for simulating wing kinematics that accounts for wing deformations and drive motor limitations was developed that shows an improved match between commanded and modeled wing kinematics. 30 In the present effort, we present an expanded simulation-based approach to designing platforms for flapping wing flight that more explicitly and rigorously considers the ways that interactions between subsystems lead to system-level performance. This is a novel approach because it tracks the evolution of system-level performance over time, rather than providing a single estimation of performance given a static vehicle state.…”
Section: Introductionmentioning
confidence: 99%